Acute administration of nutritionally sourced tryptophan increases fear recognition. - Attenburrow, M; Williams, C; Odontiadis, J; Reed, A; Powell, J; Cowen, P; Harmer, C (2003)
RATIONALE: The serotonin precursor tryptophan (TRP) has been widely used as a nutritional supplement and antidepressant. Recently, however, the use of TRP has been severely restricted due to its association with the eosinophilic myalgic syndrome, an autoimmune disorder probably caused by ingestion of a contaminant produced in certain TRP manufacturing processes. OBJECTIVES: To determine the bioavailability of a nutritional source of TRP obtained from milk protein and to assess whether administration of this material produced neuroendocrine and neuropsychological effects consistent with increased brain serotonin activity. METHODS: We studied 24 healthy subjects who ingested approximately 1.8 g of nutritionally-sourced TRP or placebo in a double-blind, parallel group, design. We carried out venous sampling for amino acid and hormone estimation and performed a test of emotional processing using a facial expression recognition task. RESULTS: The nutritionally-sourced TRP caused a substantial increase in the availability of TRP in plasma. Relative to placebo the TRP material produced some evidence of an increase in plasma cortisol, and enhanced the perception of fearful and happy facial expressions. CONCLUSIONS: A nutritional source of TRP increased the availability of TRP for brain serotonin synthesis and produced endocrine and neuropsychological changes consistent with increased brain serotonin function. The effect of TRP on emotional processing may be relevant to its reported activity in primate studies of social behaviour.